2016
DOI: 10.1016/j.geomorph.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Development and maintenance of a telescoping debris flow fan in response to human-induced fan surface channelization, Chalk Creek Valley Natural Debris Flow Laboratory, Colorado, USA

Abstract: Keyword:Alluvial fan evolution 2D debris-flow modeling Terrestrial laser scanning Geomorphic change detection Channel change has been a constant theme throughout William L. Graf's research career. Graf's work has examined channel changes in the context of natural environmental fluctuations, but more often has focused on quantifying channel change in the context of anthropogenic modifications. Here, we consider how channelization of a debris flows along a bajada has perpetuated and sustained the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 78 publications
2
20
0
1
Order By: Relevance
“…There has been no systematic survey of field-scale avulsion behavior, however, so such comparisons remain tentative at best. While spatio-temporal patterns of deposition on a few debris-flow fans have been monitored [Suwa and Okuda, 1983;Wasklewicz and Scheinert, 2016;Imaizumi et al, 2016] or reconstructed [e.g., Helsen et al, 2002;Dühnforth et al, 2008;Stoffel et al, 2008;Procter et al, 2012;Zaginaev et al, 2016], the observed patterns have not been quantitatively compared to infer general trends. There has also been little consideration to date of flow routing on debris-flow fans.…”
Section: Introductionmentioning
confidence: 99%
“…There has been no systematic survey of field-scale avulsion behavior, however, so such comparisons remain tentative at best. While spatio-temporal patterns of deposition on a few debris-flow fans have been monitored [Suwa and Okuda, 1983;Wasklewicz and Scheinert, 2016;Imaizumi et al, 2016] or reconstructed [e.g., Helsen et al, 2002;Dühnforth et al, 2008;Stoffel et al, 2008;Procter et al, 2012;Zaginaev et al, 2016], the observed patterns have not been quantitatively compared to infer general trends. There has also been little consideration to date of flow routing on debris-flow fans.…”
Section: Introductionmentioning
confidence: 99%
“…, ). One outstanding issue is that the spatio‐temporal patterns of deposition on debris‐flow fans have been monitored (Suwa and Okuda, ; Wasklewicz and Scheinert, ; Imaizumi et al. ) or reconstructed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Six TLS surveys were carried out at the study site (May 2011, May 2012, October 2012, May 2013, October 2013 and May 2014) using a Leica HDS C-10 tripod mounted scanner and following techniques documented in several previous studies (Staley et al, 2011(Staley et al, , 2014Scheinert et al, 2012;Wester et al, 2014;Wasklewicz and Scheinert, 2016). Leica HDS planar targets allow data collected at multiple scan positions in each of the field surveys to become seamlessly integrated into one point cloud through the registration process in Leica's Cyclone software.…”
Section: Data Collection and Uncertaintymentioning
confidence: 99%
“…in ArcGIS to depict the patterns of erosion and deposition across the two zones of interest (Staley et al, 2011(Staley et al, , 2014Scheinert et al, 2012;Wester et al, 2014;Wasklewicz and Scheinert, 2016).…”
Section: Geomorphic Change Detectionmentioning
confidence: 99%